The 'Islamic State' Organization: the Sunni crisis and the struggle of global jihadism - Abū-Hanīya, Ḥasan (Friedrich-Ebert-Stiftung, 2015)
This book seeks to answer a number of central questions regarding, on the one hand, the "Islamic State" (IS) as an organization, and, on the other hand, IS' relationship with Al Qaeda and Al Nusra Front. What are the main pillars of the ideology of the "Islamic State" organization? How can we explain IS' rapid expansion and their military victories in both Iraq and Syria? Are the conflicts between IS and the central Al Qaeda network linked to a struggle over power, influence, and control? Or are there fundamental ideological and political differences between the two organizations? How can IS' internal structure and assets be assessed? What are possible scenarios regarding the future of IS? What will be the impact of the international coalition? The authors aim to dismantle the "aura of obscurity" surrounding the "Islamic State" organization as well as to examine the similarities and the differences between IS and the central Al-Qaeda organization. For this, they analyze the stages and transformations IS underwent in the course of its development, including the factors behind its previous retreat and behind its recent reemergence. The book examines Al Nusra Front within the context of the current war in Syria. It discusses the internal conflicts between Al Nusra Front and IS, which ultimately led to a schism within Al-Qaeda and a struggle between two competing currents. The authors outline the ideological differences between IS and Al-Nusra Front in particular, and the Jihadi Salafist current in general.